2008
DOI: 10.1042/ba20070093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for the follow‐up of enzyme‐replacement therapy in mucopolysaccharidosis type VI disease

Abstract: MPS VI (mucopolysaccharidosis type VI) is a lysosomal storage disease in which deficient activity of the enzyme N-acetylgalactosamine 4-sulfatase [ASB (arylsulfatase B)] impairs the stepwise degradation of the GAG (glycosaminoglycan) dermatan sulfate. Clinical studies of ERT (enzyme replacement therapy) by using rhASB (recombinant human ASB) have been reported with promising results. The release of GAG into the urine is currently used as a biomarker of disease, reflecting in some cases disease severity and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Common characteristic of all these studies is the altered expression of enzymes studied, such as MMP-1 and MMP-13 (Simonaro et al 2008), MMP-12 (Ma et al 2008), as well as the two members of gelatinase family, MMP-2 and MMP-9 (Richard et al 2008;Simonaro et al 2005). Despite all this work, MMPs have not been sufficiently studied in human tissues, with the exception of one study, conducted by Di Natale et al, which revealed a downregulation of MMP-9 in patients with MPS VI (Di Natale et al 2008). Apart from the expression of MMPs, enzyme activity of these proteins is also a promising study field.…”
Section: Discussionmentioning
confidence: 93%
“…Common characteristic of all these studies is the altered expression of enzymes studied, such as MMP-1 and MMP-13 (Simonaro et al 2008), MMP-12 (Ma et al 2008), as well as the two members of gelatinase family, MMP-2 and MMP-9 (Richard et al 2008;Simonaro et al 2005). Despite all this work, MMPs have not been sufficiently studied in human tissues, with the exception of one study, conducted by Di Natale et al, which revealed a downregulation of MMP-9 in patients with MPS VI (Di Natale et al 2008). Apart from the expression of MMPs, enzyme activity of these proteins is also a promising study field.…”
Section: Discussionmentioning
confidence: 93%
“…These findings have yet to be confirmed in humans. Although one study has shown evidence of increased TNF-α gene expression in RNA from peripheral blood of a patient with MPS VI that subsequently decreased during ERT, direct measurement of serum levels was not performed [62]. It should be noted that increased levels of circulating cytokines or other inflammation-based markers could potentially reflect more broadly upon MPS disease burden rather than being biomarkers of only bone and joint disease.…”
Section: Bone and Joint Diseasementioning
confidence: 92%
“…At the age of 4 years he underwent enzyme replacement therapy with Naglazyme. On that occasion, a mutation analysis showed the presence of the nonsense mutation p.R315X (c.943C>T) in apparent homozygosity (Di Natale et al, 2008). At that time, however, the DNA of the parents was not available; only after 2 years from the initial molecular diagnosis did the family members ask for their carrier status to be defined.…”
Section: Patient and Family Studiesmentioning
confidence: 96%
“…The patient was previously diagnosed as being apparently homozygous for the p.R315X mutation found on exon 5 of the ARSB gene (Di Natale et al, 2008). Subsequently, the availability of DNA from his parents allowed us to reexamine the case.…”
Section: Dna Analysis Of the Mps VI Patient And His Parentsmentioning
confidence: 97%
See 1 more Smart Citation